Pemberian Terapi Kelompok pada Lansia di Panti Werdha Kota Salatiga - Rayanti, Rosiana Eva; de Fretes, Fiane; Desi, Desi (Poltekita: Jurnal Pengabdian Masyarakat, 2023)
The increasing number of older people in Indonesia impacts the care process. Culturally, the eldest in Indonesia are cared for by other family members. On the other hand, several older people live in nursing homes during their old age. While in the nursing home, the eldest are cared for by health workers or nursing home administrators physically, psychologically, and spiritually to maintain or improve their quality of life. However, the elderly living in three retirement homes in Salatiga City are at risk of non-communicable diseases such as hypertension (70%) and high cholesterol (23%), loneliness, and sleeplessness (41%). The purpose of the community service is to provide group activities therapy to older people living in nursing homes. The activities included cognitive exercises (drawing, writing) and psychomotor (brain gymnastics and song movements). The service results showed that the eldest expression was happy and eager to follow the activities. The involvement of students also reduces the loneliness of the eldest, who have not received visits from their families for a long time. Group therapy activities can train cognitive and psychomotor skills and reduce feelings of loneliness in the elderly.